36: ANASTOMOTIC STRICTURE AFTER IVOR LEWIS OESOPHAGECTOMY—AN EVALUATION OF INCIDENCE, RISK FACTORS AND TREATMENT. (23rd April 2022) - Koshy, R; Brown, J; Chmelo, J; Watkinson, T; Phillips, A W
Abstract: Background and aim: Anastomotic stricture is a recognised complication after oesophagectomy. It can impact on patient quality of life with some patients requiring multiple dilatations. The aim of this study was to evaluate the frequency of strictures, contributing factors and the long-term outcomes of management in patients undergoing oesophagectomy with thoracic anastomosis using a standardised circular stapled technique. Methods: All patients who underwent a two-stage transthoracic oesophagectomy with curative intent between January 2010 and December 2019 at the Northern Oesophago-Gastric Unit (NOGU) in Newcastle upon Tyne, UK were included. All patients who underwent a stapled (circular) intrathoracic anastomosis using a gastric conduit were included. Stricture incidence, number of dilatations to treat strictures and refractory stricture rate were recorded. Results: Overall 705 patients were included with 192 (27.2%) developing strictures. Refractory strictures occurred in 38 patients (5.4%). One, two and three dilatations were needed for resolution of symptoms in 46 (37.4%), 23 (18.7%) and 20 (16.3%) patients respectively. Multivariable analysis identified the occurrence of an anastomotic leak (OR 1.906, 95% CI 1.088–3.341, P  = 0.024) and circular stapler size less than 28 mm (OR 1.462, 95% CI 1.033–2.070, P  = 0.032) as independent predictors of stricture occurrence. Patients with anastomotic leaks were more likely to develop refractory strictures (13.1% vs. 4.7%, OR 3.089, 95% CI 1.349–7.077, P  = 0.008). Conclusion: This study highlighted that 27.2% of patients having a circular stapled anastomosis required dilatation after surgery. However, most strictures were successfully treated after two dilatations, but 5% of patients had longer-term problems with refractory strictures.